Analysis of the Implementation and Achievement of Al-Qur'an Hadith Education at Madrasah Ibtidaiyah Al-Bhasirah Makassar - Ismail Ismail; Fitrah Ramadhan; Al Maghvira; Isnaini Indah Maulida; Yudi Try Putra; Rosika Indri Karadona; Rahmawati Rahmawati (Edusoshum : Journal of Islamic Education and Social Humanities, 2025)
The main focus of this research is to examine the alignment between teaching practices and curriculum objectives, the role of teachers in the learning process, student engagement, and academic achievement based on the Minimum Competency Criteria (KKM). This study employs a descriptive qualitative approach through classroom observations, interviews with teachers and students, and document analysis. The results indicate that the implementation of Al-Qur’an Hadith learning at MI Al-Bhasirah is carried out in a structured manner, following clear phases of learning (introduction, core, and closing). Although most students (82%) scored above the KKM threshold, the learning process remains dominated by lecture-based methods and lacks the use of engaging instructional media. This has resulted in low student engagement and limited contextual understanding of the content of the Qur’anic verses and Hadiths. Routine muraja’ah has proven effective in reinforcing memorization, but the understanding and application of Islamic values in daily life still need to be strengthened. The findings of this study recommend the need for innovation in teaching methods and media, particularly those based on technology and contextual approaches, to improve learning effectiveness. The use of instructional videos, group discussions, case studies, and parental involvement can serve as alternative strategies to enhance the quality of Al-Qur’an Hadith education. By reinforcing affective and psychomotor aspects, the learning process can produce students who not only memorize but also understand and apply Islamic teachings in real life. This research is expected to serve as both an evaluation tool and a source of inspiration for more meaningful learning development in Islamic elementary schools